2012
DOI: 10.1098/rspb.2012.1285
|View full text |Cite
|
Sign up to set email alerts
|

Flying in the rain: hovering performance of Anna's hummingbirds under varied precipitation

Abstract: Flight in rain represents a greater challenge for smaller animals because the relative effects of water loading and drop impact are greater at reduced scales given the increased ratios of surface area to mass. Nevertheless, it is well known that small volant taxa such as hummingbirds can continue foraging even in extreme precipitation. Here, we evaluated the effect of four rain intensities (i.e. zero, light, moderate and heavy) on the hovering performance of Anna's hummingbirds (Calypte anna) under laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 29 publications
1
60
0
Order By: Relevance
“…From a biological perspective, a comprehensive framework will also entail further study of environmental effects on animal flight. For example, studies have shown that hummingbirds change their flight kinematics, such as wingbeat frequency, flapping amplitude and body orientation, to compensate for turbulence (OrtegaJimenez et al, 2014) and precipitation (Ortega-Jimenez and Dudley, 2012). Bats, in contrast, appear to avoid rain because of both sensory and energy limitations (Voigt et al, 2011).…”
Section: Understanding Flapping Flight In Its Biological Contextmentioning
confidence: 99%
“…From a biological perspective, a comprehensive framework will also entail further study of environmental effects on animal flight. For example, studies have shown that hummingbirds change their flight kinematics, such as wingbeat frequency, flapping amplitude and body orientation, to compensate for turbulence (OrtegaJimenez et al, 2014) and precipitation (Ortega-Jimenez and Dudley, 2012). Bats, in contrast, appear to avoid rain because of both sensory and energy limitations (Voigt et al, 2011).…”
Section: Understanding Flapping Flight In Its Biological Contextmentioning
confidence: 99%
“…Similarly, wet hummingbirds hovering in artificial rain for only 2 s experience mass increases of up to 4% and, in parallel with wingbeat kinematic changes, expend substantially more induced power [38]. The rate of wetting, not surprisingly, depends on exposure time and intensity of precipitation.…”
Section: Flight In Rainmentioning
confidence: 99%
“…Impacts of raindrops can generate significant downward forces on an animal's body. For example, millimetre-sized drops falling on hovering hummingbirds (figure 2b) can increase the effective downwards force by up to 2.5% of body weight, with significant effects on induced power expenditure [38]. Aerodynamic performance may also be impaired; aeroplanes flying in heavy rain experience a 50% increase in profile drag on the wings [43].…”
Section: Flight In Rainmentioning
confidence: 99%
See 2 more Smart Citations